PELAKSANAAN PERJANJIAN KEAGENAN PENJUALAN TIKET DAN UPAYA PENYELESAIAN SENGKETA DI PT. EKA SARI LORENA TRANSPORT - Fuji Utomo; Rineke Sara (Constitutum: Jurnal Ilmiah Hukum, 2023)
Bus transportation services are a type of land transportation that has a very high frequency of operation, as evidenced by the fact that buses are found on the highway all the time. PT. Eka Sari Lorena Transport is a company operating in the field of land transportation services. In running its business, it is known that there are ticket sales agents as company partners who have been officially authorized by the company through a letter of appointment as a ticket sales agent. However, in its implementation there are often violations of what has been agreed upon. The problem formulation is how to implement the agency agreement between PT. Eka Sari Lorena Transport with ticket sales agents, and how to resolve disputes in cases of default by ticket sales agents at PT. Eka Sari Lorena Transport. The research method used in this research is normative juridical, empirical in nature. The research results show that the implementation of the agency agreement between PT. Eka Sari Lorena Transport and ticket sales agents are carried out based on the provisions set by the company, basically the agreement is loose, because the agent is a working partner in running his business. However, the company has determined the terms and conditions of the agent appointment agreement. Efforts to resolve disputes in cases of default by ticket sales agents at PT. Eka Sari Lorena Transport, carried out by deliberation to reach consensus, in addition to other settlement methods permitted according to applicable laws and regulations.